Community perception of malaria in a vulnerable municipality in the Colombian Pacific (2020)
Background: Malaria primarily affects populations living in poor socioeconomic conditions, with limited access to basic services, deteriorating environmental conditions, and barriers to accessing health services. Control programmes are designed without participation from the communities involved, ignoring local knowledge and sociopolitical and cultural dynamics surrounding their main health problems, which implies imposing decontextualized control measures that reduce coverage and the impact of interventions. The objective of this study was to determine the community perception of malaria in the municipality of Olaya Herrera in the Colombian Pacific.